Habitual physical activity and sedentary behavior as predictors of dynapenia in older adults: a cross-sectional study - Santos, Lucas dos; Almeida, Cláudio Bispo de; Valença Neto, Paulo da Fonseca; Silva, Rizia Rocha; Santos, Isaac Costa; Casotti, Cezar Augusto (São Paulo Medical Journal, 2025)
BACKGROUND: Dynapenia is a risk factor of mortality. Therefore, the development of low-cost and easy-to-apply tools is essential to optimize the health surveillance actions of older people. OBJECTIVES: To compare the time spent on habitual physical activity (HPA) and sedentary behavior (SB) among dynapenic and non-dynapenic older adults and ascertain the predictive ability of these behaviors on outcome. DESIGN AND SETTING: A cross-sectional population epidemiological survey was conducted involving 208 older adults. METHODS: HPA and SB were quantified using the International Physical Activity Questionnaire, and dynapenia was identified by handgrip strength (women: 18.37 kgf; men: 26.75 kgf). RESULTS: The prevalence was 24.50%. In both sexes, dynapenic individuals reported a HPA median time of 70.00 minutes/week (min/wk), while non-dynapenic women and men reported HPA median times of 240.00 and 280.00 min/wk, respectively (P < 0.05). For SB among dynapenic individuals, a median of 388.75 min/day was observed in women and 428.57 min/d in men. In contrast, non-dynapenic women and men had 291.42 and 274.28 min/day in SB (P < 0.05), respectively. The best cutoff HPA to discriminate the outcome was 150.00 min/wk in women (sensitivity: 73.30%; specificity: 60.67%) and 140.00 min/wk in men (sensitivity, 71.43%; specificity, 61.54%). The best cutoff SB was 381.43 min/day in women (sensitivity, 53.30%; specificity, 84.80%) and 351.43 min/day in men (sensitivity, 71.43%; specificity, 73.85%). CONCLUSION: Older individuals with dynapenia spent less time on HPA and more time in SB. Furthermore, HPA was found to be a better discriminator of dynapenic individuals, and SB better discriminated non-dynapenic individuals.